Characterization of doxorubicin-sensitive and -resistant colorectal cancer cell spheroids - Melo, Maria Correia da Silva (2022)
Cancer is one of the leading causes of death worldwide. The research on tumor microenvironment has recently been gaining attention due to its important role in tumor growth, progression, and response to therapy. Because of this, the development of cancer models that resemble tumors in vivo is of great relevance to cancer research and drug development. Recently, there have been developments in the use of 3D cancer models due to their ability to mimic tumor microenvironment interactions and tumor complexity. In order to be used, these models must first be thoroughly studied. This project aimed to characterize the evolution of different types of spheroids over time. The spheroids were produced from monocultures of doxorubicin-sensitive or -resistant colorectal cancer cells, or cocultures with these cells and fibroblasts. Therefore, their study allowed the comparison between the effects of doxorubicin resistance and the influence of the tumor microenvironment (in this case represented by fibroblasts) on the development of spheroids. Different techniques, namely fluorescence microscopy, transmission electron microscopy, Western blot, and RT-qPCR, were used to assess spheroid growth, viability, hypoxia, and doxorubicin internalization. The results showed that although distinct types of spheroids have a similar growth pattern and develop a necrotic and hypoxic core, they also have some differences. Doxorubicin resistance affects spheroid condensation, while the presence of fibroblasts affects cell viability and the presence of hypoxia. As for the internalization of doxorubicin, it is affected by both doxorubicin resistance and the presence of fibroblasts. Altogether, these results show the importance of studying the interactions of tumors with their microenvironment, as well as drug resistance. However, further work is still needed to support these results.